Slumming it: Ruth Park's The Harp in the South - Genoni, Paul (Monash University Publishing, 2013)
Telling Stories explores the interaction between literary culture and the public sphere in Australia, in a series of informative, witty, intelligent and thought-provoking essays. In doing so it unearths the fascinating and changing role that literature has played in Australia’s sporting, political, civic and cultural life. The essays span many forms (fiction, memoir, letters, public lectures, theatre, cartoons, song) so that authors expressing themselves in very different ways and in different historical periods are heard in conversation for the first time. Accomplished writers and canonical texts share the pages with political milestones, cinematic breakthroughs, turning points in popular culture, largely forgotten novels and memorable musical and sporting moments, to provide a fresh, kaleidoscopic view of literary Australia. Telling Stories follows a chronological structure from 1935 to 2012, with each year (more or less) being represented with an entry (or two).